An eye for an eye and the struggle for power in the discourse of the Egyptian Arab Spring - Bogomolov, Alexander (Scripta Neophilologica Posnaniensia, 2018)
An eye for an eye and the struggle for power in the discourse of the Egyptian Arab Spring